DEVELOPMENT AND CHARACTERIZATION OF CITRUS LIMONPHOSPHOLIPID COMPLEX AS AN EFFECTIVE PHYTOCONSTITUENT DELIVERY SYSTEM: Pharmaceutical Sciences-Herbal Technology - P. UDAPURKAR, PRACHI; G. BHUSNURE, OMPRAKASH; R. KAMBLE , SANTOSH (International Journal of Life Science and Pharma Research, 2022)
The aim of the present study is to develop a complex of standardized Citrus Limon extract (SCL) and phospholipid with a goal to improve the bioavailability of its phytoconstituents. Diosmin is a flavonoid glycoside, present in Citrus Limon known to possess various therapeutic properties. The poor solubility and dissolution rate limit its oral absorption and bioavailability. The phospholipid-SCL complex was prepared using solvent evaporation method and characterized by various parameters like solubility studies, particle size determination, infrared absorption (FTIR), Differential scanning calorimetry (DSC), X-ray diffraction (XRD), Scanning electron microscopy (SEM), entrapment efficiency etc. SEM and XRD reveal the reduction in crystallinity of extract in the complex. FTIR and DSC confirm the formation of phytophospholipid complex. The in vitro dissolution studies revealed a significantly higher efficiency of complex in releasing the SCL in comparison to the pure SCL, or the physical mixture. Phospholipid complex of SCL may be of potential use in increasing the permeability and hence the bioavailability of diosmin. The result of the study revealed that the phospholipid complex may be considered as a promising drug delivery system that improves the absorption and bioavailability of plant constituents.